"This is Not Normal": Ability, Gender, and Age in the Resistance to Trumpism - McDaniel, Byrd; Renfro, Paul M. (Disability Studies Quarterly, 2019)
Since Donald Trump's formal emergence on the national political stage in 2015, many of his detractors have argued that Trump somehow belongs outside of American presidential and political history and divorced from the structural inequalities that facilitated his rise. Taking Trump as "abnormal," as the ubiquitous slogan "This is not normal" clearly does, his critics have regularly resorted to a politics of mockery, principally of pathologization, emasculation, and infantilization—fixating on his hair, hands, weight, immaturity, and even his penis size. These criticisms thereby judge Trump against a fictive, masculine, able-bodied standard of American presidential leadership, leveraging language used to stigmatize the very groups Trump's presidency stands to harm the most. The phenomenon of Trumpism, then, appears not only in the president's demagoguery, which deems certain populations suspect and deserving of surveillance, punishment, and perhaps expulsion (or even extermination); it also reveals itself in responses to such demagoguery. The present essay analyzes the ableism implicit in criticisms of Trump's masculine deficiency, physical abnormality, intellectual incapacity, and childishness. We illuminate the stakes and consequences of these criticisms and conclude by advocating for a more inclusive counterpolitics that empowers, rather than stigmatizes, the historically dispossessed groups which will suffer most acutely under Trump's revanchist regime.